Adolescents sexual practices - Frias, Ana (2013)
Introduction: If teens options are experimenting sexualized practices, we should facilitate their knowledge, make them aware of their choices and help them living their sexuality in a safer mode. Objectives: To identify adolescents sexual practices; characterize the attitudes of teenagers against the use of contraception. Methods: quantitative research with exploratory nature. We studied a convenience sample of 301 adolescents of both sexes whitch attend the 9th grade. Sexual practices and attitudes towards the use of contraception were assessed by "Contraceptive Attitude Scale" (CAS) Kyes (sd). Statistical analysis using SPSS-19, we used measures of central tendency, measures of dispersion, mean difference tests One-way ANOVA. Results: The presence of young people with sexual experience. The petting is used by the majority (62.2%), the practice of coitus are at 19.6% and auto-eroticism is denied by the majority (56.8%), while 43.2% report that their practice. For the petting and considering the sex of the subjects, there are some significant differences : (U (299) = 8004, Z = -4.14, p <.05) and the same occurs in the autoeroticism (U (299) = 1899 Z = -13.56, p <.05), in the intercourse in sexually active, there are no significant differences (U (299) = 10650.5, Z = - .233, p = .816). The consistent use of contraception is approximately (50.8%) to the inconsistent use (49.2%), with no differences according to the gender of the subjects (U (59) = 325.5, Z = -1523, p = .128) Conclusions: Alentejo region is considered as problematic in what concerns to our sample of adolescent motherhood and the risky practices coitus